Mollusks in the Mangrove Ecosystem: Exploring the Diversity of Life Among Mangrove Roots at Mangkang Beach, Tugu District, Semarang City.: - Wikrama, Altafa Ghanaya Ramadya Wikrama (Jurnal Moluska Indonesia, 2024)
Mangrove ecosystems are considered essential habitats for mollusks. The biodiversity of organisms living among mangrove roots, such as gastropods and bivalves, plays a crucial role in the ecological function of mangrove ecosystems. Mollusk diversity serves as an indicator of the richness of biodiversity in these areas. This study aims to obtain up-to-date information on mollusk diversity in the mangrove ecosystem at Mangkang Beach, Tugu District, Semarang City. The research method used was purposive sampling, which is a method of determining station locations based on specific criteria that can represent a population. The study was conducted by describing the types of mollusks found. Based on the research results, 133 mollusks were found, consisting of 9 species. The species obtained were Telescopium telescopium, Cerithideopsilla alata, Cerithidea cingulata, Cerithidea obtusa, Cassidula aurisfelis, Filopaludina sp., Pomacea canaliculata, Crassostrea virginica, and Crassostrea rhizophorae, with the dominant species being Cerithidea. The differences in mollusk abundance at each station are suspected to be caused by several factors, such as the mangrove ecosystem being located near residential areas, resulting in uneven distribution of mollusks. The difference in mangrove species also serves as an indicator of the influence on mollusk abundance in this ecosystem.